2003
DOI: 10.1351/pac200375112435
|View full text |Cite
|
Sign up to set email alerts
|

Need for establishing integrated programs to monitor endocrine active compounds

Abstract: Environmental monitoring programs on endocrine active compounds (EACs) have been used to document the level of exposure and to assess the possible association to the occurrence of developmental and reproductive disorders in wildlife. The establishment of causal links between exposure and effect data, however, was found to be difficult due to, for example, the presence of confounding factors or limited understanding of EAC mechanisms and interactions, but also because of conceptual and methodological limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Some studies reported reasonable to good correlation between estrogenic levels in surface water and the VTG response [24] or between effluent loading of the river and VTG induction in exposed fish [25,26], but a number of other studies found no clear relationship between estrogenic exposure and the VTG biomarker response [27–29]. Such discrepancies point to the need to develop further the monitoring strategies for assessment of estrogenic contamination of aquatic environments [30].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported reasonable to good correlation between estrogenic levels in surface water and the VTG response [24] or between effluent loading of the river and VTG induction in exposed fish [25,26], but a number of other studies found no clear relationship between estrogenic exposure and the VTG biomarker response [27–29]. Such discrepancies point to the need to develop further the monitoring strategies for assessment of estrogenic contamination of aquatic environments [30].…”
Section: Introductionmentioning
confidence: 99%